Estimation of the Crown Widths of Un erupted Canine and Premolars by Using Vistibulo-oral Crown Dimensions of Permanent Teeth - Hind T Jarjees (University of Mosul, College of Dentistry, 2012)
Aims: To estimate multiple regression equation on (88) subjects (48 females and 40 males),for predict-ing the widths of crowns of unerupted canine and premolar for both jaws and both genders. The sub-jects had normal class I molar relationship with full permanent dentition. Materials and methods: Plas-ter models of (88) subjects (48 females and 40 males ).Mesiodistal diameter (MMD) and vestibulooral diameter (VOD) of the crown of cental incisor, lateral incisor,canine,premolars and first molar( I1,I2,C both P1 and P2, and M1) on both sides in both jaws were measured. Multiple regression equations and correlation coefficients between the predictors( central incisor,lateral incisor and first molar) and the criteria variables (canine and premolars) were calculated. The data were analyzed by computerized statistical program SPSS. Results: Gradual regression equations were derived on the basis of measure-ment result ,by using three to five predictors to predict the sums of width of crown of unerupted canine and premolars using separated equations for both jaws and both genders (i.e four multiple regression equations were prepared).The coefficients of multiple correlations regarding gender and jaws ranged between 0.70-0.79.Conclusions: Establish regression equations, which would give satisfactory correla-tion coefficient regarding the gender and the jaw varied from 0.70-0.79